Decolonial Gestures in Canada’s Settler State: Contemporary Indigenous Writers Jordan Abel and Leanne Simpson - Kristina Aurylaite (Baltic Journal of English Language, Literature and Culture, 2017)
This paper discusses the ways recent texts by two Indigenous Canadian writers, Jordan Abel’s collection of conceptual poetry Un/Inhabited and Leanne Simpson’s short stories and poems Islands of Decolonial Love, engage in what Walter Mignolo terms ‘decolonial gestures’ to expose the workings of contemporary settler colonialism and counter their effects. The theoretical section explains the specificities of settler colonialism that make decolonization in the sense of regaining freedom from the colonizers impossible; it then discusses the possibilities for decolonization that exist in settler countries, particularly those that refer to cultural and artistic practices. The analytical section focuses on the different strategies Abel and Simpson use in their work to enact what Mignolo calls ‘epistemic disobedience.’ Abel resorts to decolonial violence in appropriating selected texts of the genre of the Western and erasing from them to undo their loaded ideological messages. Simpson’s work, marked by explicitly confrontational rhetoric, focuses on Indigenous characters and communities, foregrounding their colonial traumas and the role of traditional knowledge and cultural practices in healing them. The paper argues that the decolonial gestures Abel and Simpson undertake work to reject the mainstream rhetoric of reconciliation, inviting Indigenous people to recognize the workings of settler colonialism and look for ways of extricating from them.